One-year mortality and morbidities of severe fever with thrombocytopenia syndrome compared with other diseases: A nationwide cohort study in South Korea. - Namwoo Heo; Seok-Jae Heo; Yoon Soo Park; Seonju Yi; Hyunju Lee; Hyo-Jung Lee; Yong Chan Kim (Public Library of Science (PLoS), 2024)
Background The long-term mortality and morbidity of patients with severe fever with thrombocytopenia syndrome (SFTS) remain unclear. Methods This retrospective cohort study was conducted using the National Health Insurance Service dataset on hospitalized patients with SFTS aged ≥20 years between 2016 and 2021 (n = 1,217). Each SFTS case was matched with three controls hospitalized for non-SFTS-related diseases using propensity score matching. The all-cause mortality of patients with SFTS was evaluated during the one-year follow-up and compared with that of controls. Post-discharge events were investigated to determine the effects of SFTS on post-acute sequelae. Results Finally, 1,105 patients with SFTS and 3,315 controls were included. Patients with SFTS had a higher risk of death during the one-year follow-up than that of controls (hazard ratio [HR], 2·26; 95% confidence interval [CI], 1·82-2·81). Thirty-day mortality was significantly higher in the SFTS group (HR, 3·99; 95% CI, 3·07-5·19) than in the control group. An increased risk of death after 31-365 days was observed among controls, though this difference was significant only among patients in their 80s (HR, 0·18; 95% CI, 0·06-0·57). For post-discharge events, patients in the SFTS group exhibited a higher risk of readmission (HR, 1·17; 95% CI, 1·04-1·32) and emergency room visit (HR, 2·32; 95% CI, 1·96-2·76) than those in the control group. Conclusion SFTS induces a higher risk of short-term mortality and post-acute sequelae in hospitalized patients during a one-year follow-up than non-SFTS-related diseases. Our results provide guidance for the management of SFTS.